(untitled) (AYUSHDHARA, 2018)
Since centuries from tribes, to the rural folk and old aged people were found to depend on their traditional medicines for treatment of various ailments. But the information related to this type of medicines and its availability is still not well documented. There is an urgent need for documenting these folklore and traditional knowledge in some form before such valuable knowledge becomes inaccessible and extinct. Thattekad is famous for the Salim Ali Bird Sanctuary which has a rich and varied birdlife and rich source for many medicinal plants. A survey was carried out among the various species of medicinal plants in Thattekad region, Ernakulam District, Kerala, India. A comprehensive survey on Thattekad area with the help of local Vaidyas, Folk practitioners, expert ornithologists, Botanists, and Ayurvedic vaidyas specialised in the field of Dravya guna vijnana conducted during the period of December to February. Samples are systematically photographed and information’s from the local Vaidyas and traditional Folk practitioners are documented and analyzed by expert Ayurvedic vaidyas and Botanists. In the survey conducted, a total of 31 drugs having medicinal properties have been identified. This particular area of Western Ghats is rich with varied flora and endemic species. The present paper is an effort to fulfil the gap in the field of medicinal plants availability and to enlist existing wild medicinal plants in Thattekad region.